2022
DOI: 10.2147/copd.s374079
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Indicators for Asthma-COPD Overlap: A Systematic Review and Meta-Analysis

Abstract: Background Some clinical indicators have been reported to be useful in differentiating asthma-chronic obstructive pulmonary disease (COPD) overlap (ACO) from pure asthma/COPD, but the results were inconsistent. This study aims to evaluate the diagnostic value of these indicators for ACO. Methods Databases of PubMed, EMBASE, Ovid and Web of Science were retrieved. Pooled standardized mean differences (SMDs) with 95% confidence intervals (CIs) were calculated in random-ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…We thought the reason for this phenomenon was that the positive BDT result and exposure to tobacco smoke reduced the difference in BECs between ACO and COPD or asthma [ 34 36 ]. Peng reported that patients with ACO had higher BECs than those with COPD [ 37 ]. However, there was no difference in BECs among the asthma, COPD, and ACO groups in the real-world study cohort, NOVELTY [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…We thought the reason for this phenomenon was that the positive BDT result and exposure to tobacco smoke reduced the difference in BECs between ACO and COPD or asthma [ 34 36 ]. Peng reported that patients with ACO had higher BECs than those with COPD [ 37 ]. However, there was no difference in BECs among the asthma, COPD, and ACO groups in the real-world study cohort, NOVELTY [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although our research shows that inflammatory biomarkers can distinguish CRD, the clinical application value is still in the exploration stage. We mainly differentiate CRD according to diagnostic criteria and some clinical indicators that can reflect the characteristics of the disease (e.g., fractional exhaled nitric oxide, total immunoglobulin E, allergy tests, et al) (48)(49)(50). Inflammatory biomarkers are just another auxiliary means for the hard-to-distinguish CRD.…”
Section: Discussionmentioning
confidence: 99%
“…This exploratory pilot study used a retrospective cross-sectional design to evaluate the practical relevance of YKL-40 (and other blood parameters) to delineate between BA subjects and COPD subjects. To the best of our knowledge, such basic information is lacking in Europe and is scarce around the world [ 18 , 19 , 20 ]. Hence, a group of age- and sex- matched patients was selected in order to obtain evidence-based information about the clinical applicability of these biomarkers.…”
Section: Methodsmentioning
confidence: 99%